Generation of pig primary fibroblast cells harboring defective MC4R genes by N-ethyl-N-nitrosourea mutagenesis: A gene-driven, nontransgenic approach to pig improvement - Sakurai, Michiharu; Suzuki, Shun-ichi; Furusawa, Tadashi; Mikawa, Satoshi; Tokunaga, Tomoyuki; Onishi, Akira; Awata, Takashi (Scientific Research Publishing, 2013)
Transgenic pigs have been produced with the aim of further improving pigs in terms of economic and environmental traits, but these animals have not been allowed to enter the food chain. As an alternative approach to generating pigs with novel traits of economic importance that cannot be introduced by conventional breeding, we propose a strategy for combining in vitro mutagenesis of pig primary cells with N-ethyl-N-nitrosourea (ENU) and somatic-cell nuclear transfer (SCNT) technology. To explore the feasibility of this strategy, we treated pig primary fibroblast cells with ENU, estimated the per-base mutation frequency induced by the mutagen, clonally cultured about 4000 of the mutagenized cells, and screened them for mutation within the coding region of the melanocortin-4 receptor (MC4R) gene, a key gene in energy homeostasis. Through this screening, we obtained 14 cell clones, each harboring a heterozygous base change within the coding region for MC4R. Of the mutant cell clones, each of two contained a mutant allele encoding MC4R with greatly reduced receptor activity. By SCNT using these cell clones as donors, pigs harboring mutated MC4R alleles with reduced receptor activity can be produced. Our strategy for generating pigs with novel genetic traits likely will be more acceptable to the public than is the use of transgenic technology.
Keywords: Pig; Fibroblasts; N-Ethyl-N-Nitorosourea; Mutagenesis